Studies on HBcAg-rBlo t 5-21 Fusion Protein Vaccine That Alleviates Blomia tropicalis Airway Inflammation - Pei Y; Xiao Z; Wei S; Peng M; Luo C; Wang D (Dove Medical Press, 2022)
Yechun Pei,1- 3,* Zhengpan Xiao,1,2,* Shuangshuang Wei,1,2 Meiqi Peng,1,2 Chenghui Luo,1,2 Dayong Wang2,3 1School of Life Sciences, Hainan University, Haikou, People's Republic of China; 2Laboratory of Biopharmaceuticals and Molecular Pharmacology, School of Pharmaceutical Sciences, Hainan University, Haikou, People's Republic of China; 3One Health Institute, Hainan University, Haikou, People's Republic of China*These authors contributed equally to this workCorrespondence: Yechun Pei, Department of Biosciences, School of Life Sciences, Hainan University, 58 People's Road, Haikou, Hainan, 570228, People's Republic of China, Email ycpei@hainanu.edu.cn Dayong Wang, Laboratory of Biopharmaceuticals and Molecular Pharmacology, School of Pharmaceutical Sciences, Hainan University, 58 People's Road, Haikou, Hainan, 570228, People's Republic of China, Email wangdy@hainanu.edu.cnBackground: In tropical and subtropical areas, allergens from the dust mite species Blomia tropicalis are common causes of allergic rhinitis and asthma. Blomia tropicalis has two main allergens: Blo t 5 and Blo t 21.Aim: To generate a chimeric virus-like particle containing HBcAg, Blo t 5 and Blo t 21 that can treat allergies caused by Blomia tropicalis.Methods: To produce allergic asthma in mice, prokaryotic expression and purification of Blomia tropicalis allergens rBlo t 5, rBlo t 21, and recombinant fusion allergen rBlo t 5- 21 were utilized in the study. We created a hepatitis B core antigen (HBcAg) and rBlo t 5- 21 fusion prokaryotic expression plasmid. HBcAg-rBlo t 5- 21 was purified after expression and tested by transmission electron microscopy (TEM). Furthermore, the protein HBcAg-rBlo t 5- 21 was employed as a protein vaccination.Results: In allergy-induced mouse model experiments, the fusion allergen rBlo t 5- 21 was more effective than the individual allergens rBlo t 5 and rBlo t 21 at inducing allergy. We found that vaccinating allergic mice with the recombinant fusion protein vaccine HBcAg-rBlo t 5- 21 alleviated allergy symptoms elicited by the rBlo t 5- 21 allergen. Vaccination with HBcAg-rBlo t 5- 21 resulted in a decrease in total serum IgE levels, suppression of anaphylaxis, and reduction of inflammatory cell infiltration into lung tissue as compared to the PBS group.Conclusion: HBcAg-rBlo t 5- 21, a protein vaccine containing both the hepatitis B core antigen and the Blomia tropicalis fusion allergen rBlo t 5- 21, could be a suitable vaccination for preventing allergy disorders caused by Blomia tropicalis.Keywords: Blomia tropicalis, vaccine, hepatitis B core antigen, asthma